Therapeutic efficacy of rare earth carbonate with chemoradiotherapy in late-stage non-small cell lung cancer: a cohort prospective study - Cao, Qiang; Ye, Xia; Wu, Xinyan; Zhang, Qi; Gong, Junling; Chen, Yuquan; You, Yanwei; Shen, Jun; Qiang, Yi; Cao, Guangzhu (Frontiers in Endocrinology, 2023)
Objective:To compare the therapeutic effects and adverse reactions of sterilizing rare earth carbonate combined with concurrent chemoradiotherapy and simple concurrent chemoradiotherapy in the treatment of late-stage non-small cell lung cancer (NSCLC), and to analyze the reasons for the differences. Method:A total of 817 patients with pathologically diagnosed late-stage NSCLC from June 1, 2021 to December 30, 2022, in the affiliated hospital of Kunming University of Science and Technology, were selected. They were randomly divided into a control group of 315 people and an experimental group of 371 people. The control group was given concurrent chemoradiotherapy (cisplatin + etoposide), while the experimental group simultaneously took a low dose of sterilized rare earth carbonate (0.05mg/Kg). The χ² test and Fisher's test were used to compare the clinical pathological features, objective response rate (ORR), ECOG score, and adverse reactions of the two groups of patients, while survival analysis was used to compare the progression-free survival (PFS) of the two groups. Cox regression analysis was used to test factors related to prognosis. Results:The differences in clinical pathological features between the two groups of patients were not statistically significant, with all P>0.05. The ORR of the control group was 45.18% (178/394), and the experimental group was 89.83% (380/423), with a statistically significant difference (P=0.001). After treatment, the ECOG score of the experimental group was lower than that of the control group, P<0.001. The adverse reaction grading of patients in both groups was below level 3 after treatment, and no treatment-related fatalities occurred. The risk of pulmonary infection and bone marrow suppression in the experimental group was lower than that in the control group. Conclusion:In late-stage NSCLC patients, compared with simple concurrent chemoradiotherapy, the combination of concurrent chemoradiotherapy and sterilizing rare earth carbonate can significantly improve the short-term therapeutic effect and prognosis of patients, with good safety.